Electronic parameters for charge transfer along DNA - Hawke, L.G.D.; Kalosakas, G.; Simserides, C. (European Physical Journal E, 2010)
We systematically examine all the tight-binding parameters pertinent to charge transfer along DNA. The pi molecular structure of the four DNA bases (adenine, thymine, cytosine, and guanine) is investigated by using the linear combination of atomic orbitals method with a recently introduced parametrization. The HOMO and LUMO wave functions and energies of DNA bases are discussed and then used for calculating the corresponding wave functions of the two B-DNA base-pairs (adenine-thymine and guanine-cytosine). The obtained HOMO and LUMO energies of the bases are in good agreement with available experimental values. Our results are then used for estimating the complete set of charge transfer parameters between neighboring bases and also between successive base-pairs, considering all possible combinations between them, for both electrons and holes. The calculated microscopic quantities can be used in mesoscopic theoretical models of electron or hole transfer along the DNA double helix, as they provide the necessary parameters for a tight-binding phenomenological description based on the pi molecular overlap. We find that usually the hopping parameters for holes are higher in magnitude compared to the ones for electrons. Our findings are also compared with existing calculations from first principles.